(untitled) (REMUNOM, 2025)
This study investigated the functionality of cannabidiol (CBD) in managing behavioral manifestations associated with Autism Spectrum Disorder (ASD), considering the interface between neuroscience, behavioral psychology, and Brazilian health regulation. Recent evidence shows that CBD acts as a modulator of the endocannabinoid system, promoting reductions in irritability, aggression, anxiety, hyperexcitability, and sleep disturbances, which contributes to greater emotional stability and decreased disruptive behaviors. This effect does not replace structured behavioral interventions, but enhances therapeutic responsiveness, expanding conditions for functional learning, engagement in evidence-based therapies such as ABA, adaptive skills training, and socio-emotional development. In Brazil, its use has legal support and is regulated by ANVISA, which allows safe medical prescription, quality control, standardization, traceability, and progressive access, especially amid the increase in ASD diagnoses and the need to expand health care policies. The literature demonstrates promising clinical potential, but requires longitudinal and controlled studies to standardize protocols, dosages, and therapeutic parameters. Therefore, CBD represents a relevant complementary strategy within multifactorial care for ASD, contributing to improved global functionality, greater autonomy, promotion of inclusion, and enhancement of quality of life for the patient and their family.